How to Breathe Underwater - Skinner, Vicky (New York : Swoon Reads, 2018)
Kate’s father has been pressuring her to be perfect for her whole life, pushing her to be the best swimmer she can be. But when Kate finds her dad cheating on her mom, Kate’s perfect world comes crashing down, and Kate is forced to leave home and the swim team she's been a part of her whole life. Now in a new home and new school, faced with the prospect of starting over, Kate isn't so sure that swimming is what she wants anymore. But when she decides to quit, her whole world seems to fall apart. But when Kate gets to know Michael, the cute boy that lives across the hall, she starts to think that starting over might not be so bad. There's only one problem: Michael has a girlfriend. As the pressures of love, family, and success press down on her, can Kate keep her head above water?
Tặng
Keywords: English Literatue; Retelling Story